KONSERVASI PANTAI LABUANGKALLO DENGAN METODE MEKANIK DAN VEGETATIF - Idayati, Sri; Utomo, Wani Hadi (BUANA SAINS, 2017)
Labuangkallo is a village in costal area, located on the bay of Apar, in the boundary of57 km2 national park. Based on the map of hydro oceanography (1980) and bathymetry measurements (2011), there has been changing of coastline during 31 years.It showed significant changes, especially in the protrusion showed abrasion of 4.9507 m / yr. In the review and direct observation, the issues are grouped into three (3) major parts: (a) Labuangkallo river estuary is getting narrow due to sedimentation; (b) Fishermen settlement was eroded by waves, and (c) mangrove forest was destroyed by abrasion. The source of obstruction is, there is magnitude of the waves from the northeast and east coast, and it abrades the land, especially in area of protrusion / headland. It made angled waves against the shoreline andthe wave forces shaping currents that carry sediment along the coast due to abrasion and deposited on the edge of the river Labuangkallo. The conseravation strategy is usingmechanical method is hard treadment by coastal protector constructionand HDPE sand bag materials, there of the vegetation method with soft treadment using mangrove vegetation along the coastal village. Both are considered the strategies forreclamation.